The Role of The Principal in Developing Educational Institutions in MTsN 3 Jombang - Afiziaulhaq, M; Sirojuddin, Didin (Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to determine the role of the principal in developing educational institutions at MTsN 3 Jombang. This type of research used qualitative research. The research subjects were principals and teachers using interview, observation, and documentation methods. The results showed that the principal has carried out his duties optimally in the efforts of the Principal's Strategy for Developing Educational Institutions at MTsn 3 Jombang, the principal has two ways, the first is an effort to develop the potential of teachers, this program focuses on improving the skills of teachers in teaching students, secondly Improving the Quality of Education Through School Excellence Programs in this program focuses on increasing the potential of students by creating 3 programs namely International Excellence Service Programs, Special Talented Intelligent Services and Religious Excellence Services